Study of Neuron a Specific Enolase as Potential Biomarker for Assessing the Severity and Outcome in Patients with Cerebrovascular Accidents (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: cerebrovascular accident; ischemic stroke; hemorrhagic stroke; neuron specific enolase; brain damage